Global rebalancing in a three-country model - Philipp Engler (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2009)
This paper extends the model of Engler et al. (2007) on the adjustment of the US current account to a three-country world economy. This allows an analysis of the differential impact of a reversal of the US current account on Europe and Asia. In particular, the outcomes under different exchange rate policies are analysed. The main finding is that large factor re-allocations from non-tradables to tradables will be necessary in the US. The direction of factor re-allocation in Asia depends on whether the Bretton-Woods-II regime of unilaterally fixed or manipulated exchange rates in Asia is continued. If this is the case, the tradables sector and the current account surplus will continue to grow even when the US deficit closes. The flip side of this result is that Europe will face a huge real appreciation and an enormous current account deficit. With floating exchange rates worldwide, the impact on Europe will be limited while Asias tradables sector will shrink.
Keywords: E2; F32; F41; 330; Global imbalances; US current account deficit; dollar adjustment; sectoral adjustment